Low-dimensional nano-patterned surface fabricated by direct-write UV-chemically induced geometric inscription technique - Allsop, Thomas P.; Neal, Ronald; Kundrát, Vojtěch; Wang, C.; Mou, Chengbo; Culverhouse, Phil; Ania-Castanon, J. D.; Kalli, Kyriacos; Webb, David J. (My University, 2019)
We investigate a nano-patterning process which creates reproducible periodic surface topological features that range in size from ∼100  μm to ∼20  μm. Specifically, we have fabricated multi-layered thin films consisting of germanium/silicon strata on a planar substrate, with each layer having nanometers thickness. The material processing exploits focused 244 nm ultra-violet laser light and an opto-mechanical setup typically applied to the inscription of fiber gratings, and is based upon the well-known material compaction interaction of ultra-violet light with germanium oxides. We show this process can be extended to create arrays of metal nano-antennas by adding a metal overlay to the thin film. This results in arrays with dimensions that span nanometer- to centimeter-length scales. Also, each nano-antenna consists of "nano-blocks." Experimental data are presented that show the UV irradiance dosage used to create these metal nanostructures on D-shaped optical fibers has a direct relationship to their transmission spectral characteristics as plasmonic devices.
Keywords: Laser materials processing; Optical fiber fabrication; Optical fibers; Plasmonics